Clinical study of invasive pulmonary aspergillosis following influenza A H1N1. Issue 30 (30th July 2021) - Liu, Yi; Xie, Zuo-Zhou; Wang, Xiang; Zhu, Zheng-Hua; Yang, Chen
Abstract : Abstract: This study to analyze the clinical characteristics of patients with invasive pulmonary aspergillosis (IPA) following influenza A (H1N1) infection. We retrospectively analyzed 10 cases with IPA following H1N1 infection. The clinical manifestations, laboratory examination results, chest computed tomography, and treatments were analyzed. Clinical manifestations: all 10 cases had typical flu-like symptoms at the onset of the disease, among which 7 patients developed dyspnea in the late stage, and 8 patients had hemoptysis. Laboratory examination: the absolute and percentage of peripheral blood lymphocytes in all 10 patients were declined, among which 5 cases were with decreased CD3 + CD4 + T cells/lymphocytes; 9 cases with increased bronchoalveolar lavage fluid galactomannan; 6 cases with increased serum galactomannan; 1 case with bronchoalveolar lavage fluid cultured aspergillus fumigatus; and 2 cases with aspergillus by second-generation sequencing. Chest computed tomography: all patients showed multiple diffused ground-glass opacities at the beginning, along with linear or reticular interstitial changes. Two cases had multiple subarachnoid nodules with halo signs, 3 cases had consolidation in multiple segments of both lungs, 2 cases had cavities, and 4 cases were with pleural effusion. Treatment: 10 patients were treated with antiviral and anti-Aspergillus drugs after admission. Four patients received respiratory support. All 10 cases were cured and discharged. Early diagnosis of IPA in influenza A (H1N1) patients is the key to successful treatment.